The Arguments of Law, Policy and Practice Against Swiss-Type Patent Claims - Armstrong, Daniel (Victoria University of Wellington Law Review, 2001)
Swiss-type patent claims were first recognised by Switzerland in 1984 as a means of permitting drug manufacturers to gain patent protection following the discovery of a known substance’s second or subsequent medical use. Despite dubious legal foundations, particularly the questionable existence of sufficient novelty, Swiss-type claims have been accepted in Europe, England, and, in a recent Court of Appeal decision, New Zealand. Additionally troublesome is that the dominant reason for their acceptance has been the drive for uniformity in national patent laws, a desire that precluded consideration of the various negative practical consequences of accepting such claims. This topic has received little academic comment and this essay redresses that in the most assertive of ways by arguing that Swiss-type claims are illegal, primarily due to a lack of novelty, and that they should be illegal for various reasons of policy and practice.